Interventional cardiology imaging : an essential guide - Abbas, Amr E. (Springer, 2015)
This book provides an overview of the current available invasive coronary imaging modalities, presenting a concise review of the technologies, indications, appropriate uses, and pitfalls. Since the establishment of invasive coronary angiography, the limitations of the technique have not gone unnoticed. As a result, multiple invasive imaging modalities have been developed in an attempt to characterize the true severity of coronary artery disease, and to guide percutaneous coronary interventions. The evolution of novel interventional imaging modalities is progressively altering our understanding of coronary artery disease diagnosis and prognosis. Interventional Cardiology Imaging: An Essential Guide is an invaluable tool for interventional cardiologists and cardiologists in training who wish to have a concise and practical review of all available modalities of invasive coronary imaging.